Biomimetic processing of bioactive interface on silicon substrates - Chong, S. C. (2012)
To facilitate the implantation of silicon-based devices in vivo, the presence of a biocompatible and bioactive coating is noted to be an essential factor. The objective of this present work is therefore to explore a relatively simple and low cost process to induce the formation of bioactive apatite on silicon. The formation of apatite on silicon was carried out by a biomimetic approach on two orientations of silicon wafer, namely (100) and (111). The samples are functionalized by chemical etching, followed by incubation in a simulated body fluid. Scanning electron microscopy, energy dispersive X-ray analysis, X-ray diffraction analysis, and X-ray photoelectron spectroscopy were carried out. It was found that the growth of apatite is dependent on the orientation of the silicon wafer. Cell culturing experiment further verified the biological performance of the apatite-coated silicon samples.